Composites based on electrospun fibers modified with cellulose nanocrystals and SiO2 for selective oil/water separation. (1st January 2023) - Wang, Dong; Mhatre, Sameer; Chen, Jingqian; Shi, Xuetong; Yang, Haiying; Cheng, Wanli; Yue, Yiying; Han, Guangping; Rojas, Orlando J.
Abstract: Membranes for water remediation require structural stability, efficient operation, and durability. In this work, we used cellulose nanocrystals (CNC) to reinforce hierarchical nanofibrous membranes based on polyacrylonitrile (PAN). Hydrolysis of the electrospun nanofibers (H-PAN) enabled hydrogen bonding with CNC and provided reactive sites for grafting cationic polyethyleneimine (PEI). In a further modification, anionic silica particles (SiO2 ) were adsorbed on the fiber surfaces, obtaining CNC/H-PAN/PEI/SiO2 hybrid membranes, which developed swelling resistance (swelling ratio of 6.7 compared to 25.4 measured for a CNC/PAN membrane). Hence, the introduced hydrophilic membranes contain highly interconnected channels, they are non-swellable and exhibit mechanical and structural integrity. By contrast with untreated PAN membranes, those obtained after modification displayed high structural integrity and allowed regeneration and cyclic operation. Finally, wettability and oil-in-water emulsion separation tests demonstrated remarkable oil rejection and separation efficiency in aqueous media. Graphical abstract: Graphical abstract Unlabelled Image Highlights: CNC reinforces PAN-based hierarchical nanofibrous membranes. The integrity of the CNC/PAN membranes is improved upon hydrolysis. Modification with silica nanoparticles endows anti-swelling effects. The membranes are anti-fouling and have excellent phase separation efficiency. Long-term cyclic filtration is realized with the proposed composite membranes.